The Impact of Clickbait News on Online Media Audiences from the Perspective of Islamic Communication: A Case Study of PALTV.disway.id Palembang - Muliawan, Juan; Bukhori, K.A; Hasmawati, Fifi (AJIS: Academic Journal of Islamic Studies, 2025)
The phenomenon of clickbait news dissemination in online media has become a serious concern due to its potential influence on readers’ mindsets and behavior, particularly within Muslim communities. This study aims to analyze the impact of clickbait news on readers of PALTV.disway.id in Palembang City from the perspective of Islamic communication. The research employs a qualitative method with a descriptive approach, utilizing observation, in-depth interviews with active readers, journalists, and religious figures, as well as documentation analysis. The findings indicate that clickbait news frequently leads to information misunderstanding and a decline in the quality of readers’ Islamic understanding, especially when headlines are not aligned with the content. From the perspective of Islamic communication, such practices contradict the principles of ṣidq (truthfulness), tablīgh (transparency), and amānah (trustworthiness) in information dissemination. Another finding reveals an increased level of skepticism toward media outlets that present Islamic issues, driven by the frequent use of provocative headlines unsupported by adequate content. This study highlights the urgency of integrity in Islamic journalism and the importance of media literacy within society. The integration of digital media analysis with Islamic communication principles constitutes the originality of this research. The results are expected to provide practical contributions for media practitioners, government institutions, and da‘wah organizations in formulating more ethical communication strategies, as well as academic contributions to the development of Islamic communication studies in the digital era.